Sucrase Activity and Exopolysaccharide Partial Characterization From Three Weissella confusa Strains - Amarila Malik; Sheilla Sheilla; Wangi Firdausi; Tri Handayani; Endang Saepudin (HAYATI Journal of Biosciences, 2015)
Exopolysaccharides (EPSs) produced by lactic acid bacteria have been well known for their important economic value in food, pharmaceutical and health industries. Large extracellular enzyme sucrases are used by lactic acid bacteria to polymerize EPS, i.e. fructansucrase and glucansucrase. This study aimed to characterize sucrase activity of three Weissella confusa strains MBF8-1, MBF8-2 and MBFCNC-2(1), which were isolated previously from local beverages and their EPS products as well. All strains showed ability to form mucoid and slimy colonies by visual inspection on agar plate using raffinose as substrate suggesting that they possessed fructansucrase activity besides glucansucrase. Obtained EPS products were characterized by HPLC analysis after hydrolysis using 3% TCA at 100C for 1 hour, and by viscosity as well. All strains exhibited similar peak patterns, assuming that all of them possessed fructan EPS product. Supernatant and cell pellet were also analyzed by in situ activity assay performing periodic acid Schiff staining after polyacrylamide gel electrophoresis; only cell pellet showed sucrase activity. Viscosity observation showed that EPS products from all strains were able to increase the viscosity slightly.